2006
DOI: 10.1086/504614
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Adjustments of Sand Gazelles (Gazella subgutturosa) to a Boom‐or‐Bust Economy: Standard Fasting Metabolic Rate, Total Evaporative Water Loss, and Changes in the Sizes of Organs during Food and Water Restriction

Abstract: To test the hypothesis that desert ungulates adjust their physiology in response to long-term food and water restriction, we established three groups of sand gazelles (Gazella subgutturosa): one that was provided food and water (n = 6; CTRL) ad lib. for 4 mo, one that received ad lib. food and water for the same period but was deprived of food and water for the last 4.5 d (n = 6; EXPT(1)), and one that was exposed to 4 mo of progressive food and water restriction, an experimental regime designed to mimic condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 39 publications
0
24
0
Order By: Relevance
“…In Arabian sand gazelles, a decrease in liver, heart, and muscle masses contributed significantly to a decrease in standard fasting metabolic rate when they were foodand water-restricted. The mass of the intestine and rumen did not change, however, perhaps reflecting an adaptation of desert mammals enabling them to adjust rapidly in the event that food becomes available after rain [148]. Whether the responses involved in acclimatization to seasonal changes in food availability will be sufficient to buffer mammals against greater food deficits likely with climate change, or unpredictable changes in food resources, is not known.…”
Section: Physiological Adjustmentsmentioning
confidence: 99%
“…In Arabian sand gazelles, a decrease in liver, heart, and muscle masses contributed significantly to a decrease in standard fasting metabolic rate when they were foodand water-restricted. The mass of the intestine and rumen did not change, however, perhaps reflecting an adaptation of desert mammals enabling them to adjust rapidly in the event that food becomes available after rain [148]. Whether the responses involved in acclimatization to seasonal changes in food availability will be sufficient to buffer mammals against greater food deficits likely with climate change, or unpredictable changes in food resources, is not known.…”
Section: Physiological Adjustmentsmentioning
confidence: 99%
“…Metabolic rates are flexible and can change in response to food availability (Ostrowski et al, 2006), diet quality (Naya et al, 2007) and temperature (McKechnie, 2008), but how environmental variation is expected to affect the repeatability of metabolic rate measurements is not well understood. On the one hand, spatial and temporal environmental variability may act to reduce the repeatability.…”
Section: Introductionmentioning
confidence: 99%
“…Ostrowski et al (2006a) demonstrated that a reduced food and Table 1 Body mass, measured and expected metabolic rates and respiratory quotients of the three gazelle species measured in this study. water intake leads to a reduction in fasting metabolism in G. subgutturosa.…”
Section: Considerations On Metabolic Measurements With Ruminantsmentioning
confidence: 68%
“…Our study is no exception in not testing for this effect; instead, we simply followed the common practice of using measurements for 'RMR' that were taken after the animals had stayed in the respiration chamber for several hours (e.g. Haim and Skinner 1991;Ostrowski et al 2006a). It could be hypothesized that results higher than expected values, as in G. spekei and G. gazella in our study, might be caused by the excitement due to the unusual handling and confinement.…”
Section: Considerations On Metabolic Measurements With Ruminantsmentioning
confidence: 99%
See 1 more Smart Citation